Some properties of Escherichia Coli cultures isolated from sheeps - R. H. Gajrabekov; E. S. Erzhapova; F. S. Turlova; R. S. Erzhapova (Юг России: экология, развитие, 2015)
There were isolated 190 kinds of bacteria related to genus enterobacteria, kind of Escherichia. These isolated kinds were researched for having some facts of pathogenicity hemaglutinating ability as by D–mannosy, as by its absence, hematlogic ability, resistance to antibacterial prepirations. As a resalt were apparented that the more of strains have got traitsof pathogenisity and multiple resistance to antibiotics.